2011
DOI: 10.1186/1472-6750-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel temperature sensitive promoter in cho cells

Abstract: BackgroundThe Chinese hamster ovary (CHO) expression system is the leading production platform for manufacturing biopharmaceuticals for the treatment of numerous human diseases. Efforts to optimize the production process also include the genetic construct encoding the therapeutic gene. Here we report about the successful identification of an endogenous highly active gene promoter obtained from CHO cells which shows conditionally inducible gene expression at reduced temperature.ResultsBased on CHO microarray ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…Thus, specific enhancement of the target gene transcription at 32°C by using MCRE is a promising method to increase the final yield of recombinant proteins in various cell lines. Interestingly, Thaisuchat et al [21] have recently identified a novel temperature sensitive promoter (222 bp long) in the S100a6 (calcyclin) gene, which comprises two Sp1 sites.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, specific enhancement of the target gene transcription at 32°C by using MCRE is a promising method to increase the final yield of recombinant proteins in various cell lines. Interestingly, Thaisuchat et al [21] have recently identified a novel temperature sensitive promoter (222 bp long) in the S100a6 (calcyclin) gene, which comprises two Sp1 sites.…”
Section: Discussionmentioning
confidence: 99%
“…The other approach is to regulate the ST6Gal I expression. Introduction of regulatory expression system into CHO cell, i.e., Tet-on/off system (Chung et al 2004) and the temperature-sensitive promoter (Thaisuchat et al 2011), would be effective in minimizing the disadvantage of ST6Gal I overexpression. In addition, a recent report indicated that therapeutic antibodies produced by CHO cells often contain the non-human sialic acid, N-glycolylneuraminic acid (Neu5Gc), to which Neu5Gc-specific human antibodies show antigenicity (Ghaderi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach is very labor-intensive and can yield potentially confounding results. Other methods include screening the flanking regions of highly expressed genes obtained from CHO microarray data for potential promoter candidates; this approach, however, limits identification to known genes (Thaisuchat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%